2020
DOI: 10.1177/2515127420946036
|View full text |Cite
|
Sign up to set email alerts
|

Independence in the Making: Using Makerspace Experiences to Build Foundational Entrepreneurial Competencies

Abstract: This paper describes the makerspace challenge, an experiential assignment that builds foundational entrepreneurial competencies through the creation of artifacts within campus makerspaces. This assignment strengthens student ability to navigate ambiguity, learn new technologies, effectively utilize resources, and bring creative ideas to reality in a low stakes supportive environment. Students choose 3 out of 4 pre-identified projects to complete outside of class over a three week period, presenting a tangible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…It affords the opportunity for students to acknowledge the needs of their peers helping them to develop a sense of connection with, and appreciation for, others (Jang et al, 2016b; Ryan and Deci, 2000). It is proposed that, by visually and verbally presenting their ideas in ‘gallery’ style format, students can learn from the work of others through the process of simultaneous reporting (Kennedy et al, 2020; Michaelsen and Sweet, 2008). Indeed, it is suggested that this collaborative form of activity, alongside poster type presentations, has the greatest value adding potential for student engagement (Balan and Metcalfe, 2012).…”
Section: Activity Outline: Building An Entrepreneurial ‘Learner Profile’mentioning
confidence: 99%
“…It affords the opportunity for students to acknowledge the needs of their peers helping them to develop a sense of connection with, and appreciation for, others (Jang et al, 2016b; Ryan and Deci, 2000). It is proposed that, by visually and verbally presenting their ideas in ‘gallery’ style format, students can learn from the work of others through the process of simultaneous reporting (Kennedy et al, 2020; Michaelsen and Sweet, 2008). Indeed, it is suggested that this collaborative form of activity, alongside poster type presentations, has the greatest value adding potential for student engagement (Balan and Metcalfe, 2012).…”
Section: Activity Outline: Building An Entrepreneurial ‘Learner Profile’mentioning
confidence: 99%
“…Basically, the village wants to take advantage of the various events and companies each within the village and the people around it with the aim of achieving dreams related to business improvement. (Kennedy et al, 2020).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Moreover, entrepreneurs tend to be self-reliant and independent (Kennedy et al, 2020) for they must be able to work on their own and need less social support than non-entrepreneurs. Within the Indonesian setting, dependence on the superior is reflected in the adage "asal bapak senang" -which means "keep fathers happy" -a tendency in which people please the boss for the sake of saving their socio-economic positions (Dick, 2019).…”
mentioning
confidence: 99%